2022
DOI: 10.3390/plants11131657
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production and Predicted Ethanol Yield Are Linked with Optimum Photosynthesis in Phragmites karka under Salinity and Drought Conditions

Abstract: Plant photosynthesis and biomass production are closely associated traits but critical to unfavorable environmental constraints such as salinity and drought. The relationships among stress tolerance, photosynthetic mechanisms, biomass and ethanol yield were assessed in Phragmites karka. The growth parameters, leaf gas exchange and chlorophyll fluorescence of P. karka were studied when irrigated with the control and 100 and 300 mM NaCl in a nutrient solution and water deficit conditions (drought, at 50% water h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Salinity stress can inhibit metabolic processes and result in early aging and cell death. Plants respond to salt stress through the closure of stomata, inhibition of cell expansion, and reduction of root surface area to reduce ion uptake [7].…”
Section: Salinity Drought and Flooding As Abiotic Stressesmentioning
confidence: 99%
“…Salinity stress can inhibit metabolic processes and result in early aging and cell death. Plants respond to salt stress through the closure of stomata, inhibition of cell expansion, and reduction of root surface area to reduce ion uptake [7].…”
Section: Salinity Drought and Flooding As Abiotic Stressesmentioning
confidence: 99%
“…The Fv/Fm indicates the level of photoinhibition [88]. In this study, the Fv/Fm remained stable across both ecotypes under the two treatments, which indicated that there was little photoinhibition; this suggests that both ecotypes can adapt photosynthetically to salt stress [89,90]. A more substantial increase in NPQ in the terrestrial ecotype was observed under the salt treatment, which protected the photosynthetic apparatus from damage by dissipating excess light energy in the form of heat through non-photochemical processes [90].…”
Section: Effects Of Salt Stress On the Chlorophyll Content And Fluore...mentioning
confidence: 53%
“…The sharper reduction in the Y(II), qL, and ETR of the non-halophyte line under NaCl treatment indicates that its PSII reaction center is more susceptible to damage and inactivated to a greater extent than that of the halophyte. We also observed a greater increase in NPQ in the non-halophyte under salt treatment, which protected the photosynthetic apparatus from damage by dissipating excess light energy in the form of heat through nonphotochemical processes(Wei et al 2006; Moinuddin et al2017;Abideen et al 2022). Salt stress may disrupt the biochemistry of photosynthesis, which decreases the e ciency of PSI and PSII owing to disturbances in the integrity of chloroplasts(Ibrahim et al 2015;Stadnik et al 2022…”
mentioning
confidence: 61%